WAYS OF "DOING LITERACY" IN YOUTH AND ADULT EDUCATION. APPROPRIATION OF INSTITUTIONAL LITERACY PRACTICES IN AN ADULT SECONDARY SCHOOL - Laura Eisner (Universidad Nacional del Nordeste, 2022)
This paper analyses literacy practices in intervention projects carried out by small groups of students in a secondary school for adults. Using an ethnographic approach, we reconstruct school literacy events and the textual trajectory of the texts produced by two groups of students. We analyze the strategies used by each group in trying to grapple with an unfamiliar discursive genre, deploying a variety of literacy resources and negotiating towards a final version validated by the teachers. The analysis shows that the two groups appropriate the project genre through different resolutions (either drawing on familiar literacy practices or exploring tentatively a set of new genre-related resources), while they experience learning through participation in the collective writing process. We conclude that, in adult education classrooms, interactions around writing lead to various "contact phenomena" -namely, hybridisation and border-crossing between institutional and everyday literacy practices- that enable interstitial spaces fertile for learning.